2020
DOI: 10.1111/srt.12939
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of protein denaturing activity in the effect of surfactants on skin barrier function

Abstract: Background/purpose Detailed information on the mechanism by which surfactants affect the skin barrier function is still scarce. We investigated the contribution of protein denaturation to the effect of surfactants on barrier function. Methods The Transmission Index method, which evaluates the actual effect of surfactants on barrier function, was combined with a microplate assay measuring protein denaturation activity. The correlation between the TI value and the reciprocal of the median effect concentration (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Kubota et al 27,28 reported that TEA cocoyl glutamate decreased the skin barrier function and may also increase skin permeability. Glutamate surfactant‐induced skin hyperpermeability may be associated with metal ion influx into the stratum corneum, resulting in irritant dermatitis 27,28 . DLGL is a new, gemini‐type surfactant‐containing sodium lauryl glutamate, an anionic surfactant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kubota et al 27,28 reported that TEA cocoyl glutamate decreased the skin barrier function and may also increase skin permeability. Glutamate surfactant‐induced skin hyperpermeability may be associated with metal ion influx into the stratum corneum, resulting in irritant dermatitis 27,28 . DLGL is a new, gemini‐type surfactant‐containing sodium lauryl glutamate, an anionic surfactant.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate surfactant-induced skin hyperpermeability may be associated with metal ion influx into the stratum corneum, resulting in irritant dermatitis. 27,28 DLGL is a new, gemini-type surfactant-containing sodium lauryl glutamate, an anionic surfactant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation